Inhibition of creatine kinase activity by ethylene oxide. Issue 1 (January 1990) - Matsuoka, M; Igisu, H; Inoue, N; Hori, H; Tanaka, I
Abstract : Exposure of rats to 500 ppm ethylene oxide for six hours a day, three times a week, for 12 weeks, lowered serum creatine kinase activity by more than 40%. The only other change was a slightly decreased triglyceride concentration. After four weeks of exposure, neither aspartate aminotransferase nor lactate dehydrogenase activity in brain, spinal cord, and muscle was affected but creatine kinase activity was clearly inhibited. In vitro, ethylene oxide inhibited creatine kinase activity in brain homogenate and in a purified muscle enzyme preparation. Dithiothreitol did not counteract the effect of ethylene oxide. Though the amount of sulphydryl groups in purified creatine kinase was decreased considerably by exposure to ethylene oxide, the enzyme still showed moderate activity. Thus ethylene oxide inhibits creatine kinase activity in vivo and in vitro and the inhibition appears to be unrelated to the disruption of sulphydryl groups in the enzyme.